Branch blight and dieback of walnut (Juglans regia L.) caused by Rhytidhysteron juglandis sp. nov. and its endophytic biocontrol agent Granulobasidium vellereum - Zhao, Li-Li; Zhang, Lin; Jiao, Ning; Li, Ming; Zhang, Ying (Phytotaxa, 2025)
English walnut (Juglans regia L.) is known for its health benefits and has been widely cultivated in China. Walnut branch blight and dieback are common diseases in walnut plantations. A survey was conducted at walnut plantations in Beijing, China to identify the causal agents of the disease. Six isolates were retrieved from diseased or dead branch samples of English walnut. DNA sequence analyses based on concatenated ITS, LSU, and tef1-α loci, the isolates were identified as a new fungal species, Rhytidhysteron juglandis sp. nov. Endophytic Granulobasidium vellereum isolated from healthy walnut branches, has shown potential as a biological control agent against R. juglandis. Antagonistic assays by dual cultures and walnut branches have demonstrated that G. vellereum significantly inhibits the colony or disease lesion expansion caused by R. juglandis.